Studi Kasus: Asuhan Keperawatan Jiwa dengan Kecemasan pada Orang Dewasa Menerapkan Cognitive Behaviour Therapy (CBT): Case Study: Mental Health Nursing with Anxiety in Adults Applying Cognitive Behavior Therapy (CBT) - Marisca Agustina; Hari Ghanesia Istiani; Yunia Perdanasari (Journal of Nursing Education and Practice, 2021)
Introduction: Anxiety that often occurs during a pandemic can cause a decrease in health conditions, quality of life and feelings of discomfort so that people experience obstacles in the process of life. Objectives: This study aims to determine the effect of Cognitive Behavior Therapy on anxiety during the pandemic. Method: The design in this study is a case study design using a nursing process approach. The sample in this study was Mrs. E. The sampling technique used was simple random sampling. The study was conducted in the Bogor area in August 2020. The data was collected by means of interviews, observations, and documentation studies. The research instrument was the researcher himself with the tools of a sphygmomanometer, stethoscope, thermometer, penlight, as well as assessment guidelines and Cognitive Behavior Therapy guidelines. The nursing process approach carried out by researchers includes the following stages: Assessment Researchers collect data, both from respondents/patients. Nursing diagnoses, make nursing interventions, carry out implementation and then carry out nursing evaluations. Result: After 5 visits to the client's home, the anxiety level was reduced with an anxiety score from an initial score of 25 (moderate anxiety) to 19 (mild anxiety), when the anxiety came the client applied what the nurse had taught, namely doing deep breathing assisted by the family, applying techniques Cognitive Behavior Therapy, and clients are able to carry out activities at home such as cleaning the house, cooking and when leaving the house always pay attention to health protocols. Conclution: Most of the clients who got anxiety disorder problems with Cognitive Behavior Therapy (CBT) were resolved.